How Technology Life Cycles Increase the Financial Position of the Firm (American Journal of Management, 2021)
Businesses need to understand the importance of technology life cycles for increasing their financial position. It is extremely important to understand technology life cycle approaches for gaining competitive advantage and increasing the value of the firm. The technology life cycle seeks to predict the adoption, acceptance, and eventual decline of new technological innovations. Understanding and effectively estimating technology life cycle allows for a more accurate reading of whether and when research and development costs will be offset by profits. The purpose of this paper is to provide a review of the theory, and to discuss the continued relevance of technology life cycles as they relate to competitive advantage and improved financial performance.
Keywords: management; technology; life cycle; innovation